Isolation of Skin Leukocytes Uncovers Phagocyte Inflammatory Responses During Induction and Resolution of Cutaneous Inflammation in Fish - Soliman, Amro M.; Yoon, Taekwan; Wang, Jiahui; Stafford, James L.; Barreda, Daniel R. (Frontiers in Immunology, 2021)
Leukocytes offer a critical layer of protection to the host following skin infections. Delineating the kinetics of cutaneous leukocyte recruitment as well as their anti-microbial and regulatory profiles is challenging since it requires the isolation of adequate cell numbers and maintenance of their functional properties. Herein, we took advantage of a modified procedure to gain insights into the contributions of fish phagocytes through induction and resolution phases of acute inflammation against an Aeromonas veronii cutaneous infection. Our data shows early upregulation of pro-inflammatory cytokines and chemokines, which was paired with neutrophil-dominant leukocyte migration of neutrophils from circulation to the infection site. Recruited neutrophils were associated with high levels of reactive oxygen species (ROS). Following pathogen elimination, a reduction in ROS levels and increased apoptotic cell death preceded the resolution of inflammation. These results provide a better understanding of the cutaneous immune response towards A. veronii infection. The increased viability and functionality of isolated skin leukocytes also opens the door to better understand a range of additional skin diseases.